The Influence of Organizational Culture and Intrinsic Motivation on Employee Performance Through Organizational Commitment as an Intervening Variable - Fitriyana, Ade; Prahiawan, Wawan; Kambara, Roni (Management Science Research Journal, 2023)
The purpose of this research to determine influence of organizational culture and intrinsic motivation on employee performance through Organizational Commitment. Independent variable in this research are organizational culture and intrinsic motivation, dependent variable is employee performance, and intervening variabel is organizational commitment. This research is held in Kantor Kementerian Agama Kota Serang. The Sample was taken 100 (one hundred) respondents. The primary data were collected using a questioner with analyzed by SEM (Structural Equation Modelling) statistic tools. The results of that analysis have been carried out, the results show that organizational culture has a positive and significant influence on employee performance, the intrinsic motivation has a positive and significant influence on employee performance, organizational commitment has a positive and significant influence on employee performance.